Sensor Modeling of a Vibration Sensor - Mitra Djamal (Indonesian Journal of Physics, 2006)
A new type of vibration sensor based on flat coil element has been made. A sensor modeling based on a polynomial model for determining frequency and amplitude of the sensor has been developed. The model shows a good result with relative error under 6%.